2023
DOI: 10.1037/pspp0000439
|View full text |Cite
|
Sign up to set email alerts
|

Regional personality differences predict variation in early COVID-19 infections and mobility patterns indicative of social distancing.

Abstract: The early stages of the COVID-19 pandemic revealed stark regional variation in the spread of the virus. While previous research has highlighted the impact of regional differences in sociodemographic and economic factors, we argue that regional differences in social and compliance behaviors-the very behaviors through which the virus is transmitted-are critical drivers of the spread of COVID-19, particularly in the early stages of the pandemic. Combining self-reported personality data that capture individual dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 145 publications
4
8
0
Order By: Relevance
“…Relating our results to prior work on COVID‐19 infection rates (see Peters et al., 2023) suggests that both openness and extraversion may play dual roles over time. Regions with higher openness or extraversion may have people more willing to flout lockdown restrictions and hence spread infection; however, these same regions—or the people in them—may be among the first to adopt a new vaccine regimen.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Relating our results to prior work on COVID‐19 infection rates (see Peters et al., 2023) suggests that both openness and extraversion may play dual roles over time. Regions with higher openness or extraversion may have people more willing to flout lockdown restrictions and hence spread infection; however, these same regions—or the people in them—may be among the first to adopt a new vaccine regimen.…”
Section: Discussionsupporting
confidence: 82%
“…Regarding implications, the present findings suggest that interventions aiming to promote vaccination might consider committing more resources to states on the lower ends of the openness and extraversion spectra, because people in those states are less likely to have been vaccinated. Of course, the states scoring highest on the openness and extraversion spectrum may be the exact same states or regions to experience early increases in infections in the next epidemic—or eventual pandemic (see Peters et al., 2023)—suggesting that promoting early vaccination there might be key.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other findings indicated that preventive behavior was associated positively with Agreeableness ( Chan et al, 2020 ; Muto et al, 2020 ; Qian and Yahara, 2020 ; Zajenkowski et al, 2020 ; Krupić et al, 2021 ; Pilch et al, 2021 ), Conscientiousness ( Carvalho et al, 2020 ; Chan et al, 2020 ; Nofal et al, 2020 ; Qian and Yahara, 2020 ; Krupić et al, 2021 ; Abdelrahman, 2022 ), Negative Emotionality ( Chan et al, 2020 ), and Open-Mindedness ( Qian and Yahara, 2020 ; Pilch et al, 2021 ), and negatively with Extraversion ( Krupić et al, 2021 ). Similar results were reported by Peters et al (2023) , commenting that, albeit with some exceptions, individual differences in the Big Five traits are linked with a range of COVID-19-related behaviors, like social distancing ( Bogg and Milad, 2020 ; Aschwanden et al, 2021 ; Zettler et al, 2021 ), compliance with hygiene rules ( Blagov, 2021 ; Zettler et al, 2021 ), and adherence to lockdown restrictions ( Zajenkowski et al, 2020 ; Götz et al, 2021 ; Siritzky et al, 2022 ). However, the results are not always consistent.…”
Section: Literature Reviewsupporting
confidence: 81%